2019
DOI: 10.15850/amj.v6n3.1613
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intelligence based on Short-term Memory Test between Urban and Rural Children

Abstract: Background: Cognitive development occurs during childhood and this development is influenced by various environmental factors such as urban and rural environments which can affect child cognitive development. Short-term memory is very important as the first step in processing new information to do cognitive tasks. The aim of this study was to compare the short-term memory of children coming from an urban and rural area. Methods: A cross-sectional design was performed in this observational analytical study, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Research on urban and rural school students has been extensively conducted. For instance, Addiniya et al (2019) studied the comparison of intelligence based on short-term memory tests between urban and rural children. The results of the study show that the quality of the method needs to be improved to develop the intelligence of rural students.…”
Section: Education In Rural and Urban Schoolmentioning
confidence: 99%
“…Research on urban and rural school students has been extensively conducted. For instance, Addiniya et al (2019) studied the comparison of intelligence based on short-term memory tests between urban and rural children. The results of the study show that the quality of the method needs to be improved to develop the intelligence of rural students.…”
Section: Education In Rural and Urban Schoolmentioning
confidence: 99%
“…17 The research that was conducted by Horiuchi et al 18 in Cambodia in 2018 on the differences of the nutritional status in urban and rural areas of schoolage children found that the children in rural areas had a higher prevalence of stunting than urban areas, this was highly associated with the differences of food intake between the two regions. Another research that was conducted by Addiniya et al 19 in 2014 on the comparison of intelligence based on short-term memory tests in urban and rural students in Jatinangor Region using digit span forward, digit span backward and symbol digit modality tests found that the digit span backward and symbol digit modality tests in children in urban areas were scored higher than those children in rural areas. This shows that stunting rates and short-term memory abilities of elementary school students differ between urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%